Absence of the Higuchi bound in a family of alternative linear massive spin-2 models - Fortes, Hemily G. M.; Alves, Márcio E. S. [UNESP] (IOP Publishing, 2022)
There is a well known result from the Fierz-Pauli (FP) theory in de Sitter background, it is the existence of a lower bound for the mass m of the spin 2 particle, the Higuchi bound. It establishes that m 2 ≥ 2H 2, where H is the Hubble parameter, in order to the theory presents no ghost-like instabilities. In this sense, m should be unacceptable high in order to fulfill this condition at the time of the inflationary epoch of the Universe, posing a difficulty to conciliate the FP theory with cosmology. In this article we show that the Higuchi bound can be circumvented in an alternative description of massive spin-2 particles known as L(a1) models. In maximally symmetric spaces the theory has two free parameters which can be consistently chosen in order to make the model absent of a lower bound for m. Then, m can be arbitrarily smaller than the energy scale of inflation avoiding instabilities at that time.
Keywords: gravitation; graviton; Higuchi; modified theories of gravity